Non-burn-through type solar cell conductive paste, method, electrode and cell

By using non -firing puwee and laser treatment techniques in solar cells, the aluminum thorn problem caused by silver aluminum slurry is solved, and efficient Om contact and stable battery performance are achieved, which improves the opening pressure of solar cells and Conversion efficiency.

CN119361212AInactive Publication Date: 2025-01-24西安宏星电子浆料科技股份有限公司
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411938131.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the existing solar cell processes, silver aluminum paste is prone to form aluminum splints during melting and recrystallization, resulting in increased carrier recombination, reduced open circuit voltage, and even punctured the PN junction of the solar cell, destroying the structure and reducing the conversion efficiency.

Method used

A non-burn-through conductive slurry is used, including glass powder, silver powder and organic carrier. By optimizing the composition and ratio of glass powder and combining with laser processing technology, a stable compound layer and nano-scale conductive channels are formed to reduce aluminum thorns. formation, optimizing ohmic contact.

Benefits of technology

The high open pressure and solar cell conversion efficiency are achieved, the opportunity for formation of aluminum thorns is reduced, the SIN membrane layer is protected, and the wear resistance and weather resistance of solar cells are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361212A_ABST
    Figure CN119361212A_ABST
Patent Text Reader

Abstract

The invention discloses a non-burn-through type solar cell conductive paste, a method, an electrode and a cell, and relates to the technical field of solar cells. The conductive paste comprises the following components in percentage by weight: 0.5%-5% of glass powder, 80%-90% of silver powder and 5%-15% of an organic carrier, the glass powder comprises the following components in percentage by weight: 40-70% of lead oxide, 5-20% of zinc oxide, 1-15% of silicon dioxide, 1-15% of bismuth oxide, 5-20% of aluminum oxide, 0-5% of tungsten oxide, 0-5% of gallium oxide, 0-5% of lithium carbonate, 0-5% of sodium carbonate and 0-5% of magnesium oxide. The conductive paste is a non-burn-through type conductive paste, through reasonable matching of the components and the proportion of the glass powder and further cooperation of laser-assisted sintering technology treatment, the effect of reducing carrier recombination on the SiN antireflection film layer can be greatly protected, and therefore the purposes that the open voltage is higher and the photoelectric conversion efficiency of the solar cell is higher can be achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of solar cells, and in particular to a non-burn-through solar cell conductive paste, method, electrode and battery. Background Art

[0002] Solar power generation technology has developed rapidly with the shortage of traditional fossil energy and people's attention to carbon dioxide emissions. As the main body of solar power generation technology, crystalline silicon solar cell technology has also been a focus of attention. In addition to the carrier concentration, distribution, mobility, etc. in crystalline silicon materials, the quality of solar cells is also affected by the electrical properties of the positive and negative electrodes of solar cells. Among them, the front electrode (negative electrode) has a direct impact on the series resistance, conduction resistance, fill factor, photoelectric conversion efficiency, etc., so the quality of the front electrode conductive paste determines the performance of solar cells.

[0003] TOPcon (Tunnel Oxide Passivating Contacts) process has gradually become the mainstream high-efficiency solar cell process. TOPcon solar cells are different from the current PERC (Passivated Emitter and Rear Cell) cells. They are mainly made of N-type silicon wafers. Therefore, the front electrode conductive paste uses silver-aluminum paste. The mixing of aluminum is to improve the ohmic contact of the conductive paste on the front side. However, aluminum is very easy to form aluminum thorns during the melting and recrystallization process, which aggravates carrier recombination, reduces the open circuit voltage of the solar cell, and even punctures the PN junction of the solar cell, destroying the solar cell structure and reducing the conversion efficiency of the solar cell.

[0004] The LECO (Laser-Enhanced Contact Optimization) process irradiates solar cells with high-intensity lasers while applying a deflection voltage of 10V or more. The resulting local current of several amperes significantly reduces the contact resistance between the metal and the semiconductor. Additional efficiency gains can be achieved by using laser-assisted sintering special silver paste.

[0005] In addition, in the solar cell structure, in order to improve the light transmittance, it is necessary to prepare a SiN film anti-reflection and anti-reflection layer on the surface. The SiN film anti-reflection and anti-reflection layer can also reduce the surface carrier recombination. However, since the SiN film is an insulator, it blocks the movement of carriers from the surface of the solar cell to the silver grid line, that is, it hinders the formation of ohmic contact between silver and silicon. In order to form a good ohmic contact, the traditional method uses burn-through silver aluminum paste to corrode the SiN film layer, and often over-corrosion is performed to ensure the formation of a good ohmic contact. However, this method increases the carrier recombination on the silicon surface, affects the photoelectric conversion efficiency of the solar cell, and reduces the opening voltage of the solar cell. Summary of the invention

[0006] In order to solve the problem that the prior art causes the start-up voltage of solar cells to be reduced, the present application provides a non-burn-through solar cell conductive paste, method, electrode and battery. The non-burn-through solar cell conductive paste is a conductive paste that can take into account both higher start-up voltage and higher solar cell conversion efficiency. It does not need to add aluminum powder, thereby reducing the chance of aluminum thorn formation and further improving the start-up voltage of the solar cell.

[0007] In a first aspect of the present application, a conductive paste is provided, including glass powder, silver powder, and an organic carrier.

[0008] In terms of weight percentage, it includes the following components: Glass powder 0.5%~5%, Silver powder 80%~90% and Organic carrier 5%~15%.

[0009] The glass powder includes the following components, calculated by weight percentage: Lead oxide 40%~70%, Zinc oxide 5% to 20%, Silicon dioxide 1% to 15%, Bismuth oxide 1%~15%, Alumina 5% to 20%, Tungsten oxide 0%~5%, Gallium oxide 1% to 5%, Lithium carbonate 0%~5%, Sodium carbonate 0%~5%, Magnesium oxide 0%~5%.

[0010] The present invention optimizes the composition and ratio of glass powder and the application of laser processing technology, so that the conductive paste can comprehensively achieve higher opening voltage and higher solar cell efficiency. The LECO technology reduces the contact resistance between metal and semiconductor, improves the fill factor, and further improves the efficiency of solar cells.

[0011] The stable compound layer formed by the reaction of glass powder and silicon wafer, as well as the nano-scale tiny conductive channels between silver and silicon, enhance the wear resistance and weather resistance of solar cells. Since the ohmic contact of the front electrode prepared by the conductive paste can be formed by laser-excited silver silicon diffusion, the effect of aluminum is reduced, so the aluminum powder content in the paste can be reduced, thereby reducing the chance of aluminum thorn formation.

[0012] By properly matching the composition and ratio of glass powder, the corrosion degree of SiN film layer can be precisely controlled to maintain its effect of reducing carrier recombination, thereby protecting the performance of solar cells. The conductive paste of the present invention is compatible with the existing solar cell manufacturing process, and the efficiency can be improved without making major changes to the production line.

[0013] Some of the implementation examples are listed below in terms of weight percentage of glass powder.

[0014] Lead oxide 40%~65%, Zinc oxide 10%~20%, Silicon dioxide 3% to 8%, Bismuth oxide 3% to 8%, Alumina 8% to 15%, Tungsten oxide 0%~4%, Gallium oxide 1% to 4%, Lithium carbonate 0%~4%, Sodium carbonate 0%~3%, Magnesium oxide 0%~3%.

[0015] Some of the implementation examples are listed below in terms of weight percentage of glass powder.

[0016] Lead oxide 45%~60%, Zinc oxide 10%~15%, Silicon dioxide 5% to 8%, Bismuth oxide 5% to 8%, Alumina 12% to 15% and Gallium oxide 1%~3%. In some embodiments, the average particle size of the silver powder is 1 μm to 5 μm, and the specific surface area is 0.25 to 0.5 m 2 / g; The size of the silver powder can optimize the conductive performance. The silver powder within this particle size range can form a relatively dense stack, which is conducive to the formation of a continuous conductive network during the sintering process. At the same time, the appropriate particle size can also ensure good contact between the silver powder particles, thereby reducing the contact resistance and improving the conductive performance. When preparing conductive paste, the silver powder within this particle size range is easy to mix evenly with components such as organic carriers and glass powder, which is conducive to the preparation and printing of the paste.

[0017] In some embodiments, the average particle size of the glass powder is 0.5 μm to 3 μm, and the softening point is 300 to 450°C. The glass powder in this softening point range can match the sintering temperature in the solar cell manufacturing process, ensuring that the glass powder can be fully melted and react with the substrates such as silver powder and silicon wafers during the sintering process. The moderate softening point allows the glass powder to melt and solidify quickly during the sintering process, thereby shortening the production cycle and improving production efficiency.

[0018] In some implementation examples, the organic carrier includes one or more of a resin, a solvent, and a surfactant; Furthermore, the resin is one or more of polyvinyl alcohol type butyral resin, acetate type cellulose butyrate resin, rosin type resin and acrylic resin; Further, the solvent is one or more of propylene glycol methyl ether acetate, propylene glycol butyl ether acetate, butyl carbitol, ethylene glycol monobutyl ether acetate, petroleum ether and dimethyl adipate; Furthermore, the surfactant is one or more of polydimethylsilicone oil, silicone surfactant, polyoxyethylene surfactant, oleamide, erucamide, dimethyl sulfoxide and polyether modified silicone oil; In some embodiments, the organic carrier is calculated in weight percentage and includes the following components: Polyvinyl butyral resin 5% to 10%, Cellulose acetate butyrate resin 1% to 5%, Rosin resin 2% to 10%, Acrylic resin 2% to 15%, Solvent 60%~89.5%, Surfactant 0.5%~3%.

[0019] A second aspect of the present application provides a front electrode, comprising a solar cell silicon substrate and a conductive layer disposed on the solar cell silicon substrate, wherein the conductive layer is formed by printing and sintering the conductive paste described in the first aspect.

[0020] The conductive paste and preparation method thereof provided by the present invention achieves improvement in solar cell efficiency, enhancement in wear resistance and weather resistance, reduction in the chance of aluminum thorn formation, and control of SiN film corrosion by optimizing the composition and ratio of glass powder and applying laser processing technology.

[0021] The third aspect of the present application provides a method for preparing a front electrode of a solar cell, comprising the following steps: Printing the conductive paste described in the first aspect onto the surface of the silicon substrate of the solar cell, drying, and sintering to prepare an intermediate film; The intermediate film is subjected to laser sintering treatment to prepare a conductive layer.

[0022] Optionally, the sintering conditions include: setting the temperature to 800°C to 830°C; Optionally, the laser sintering treatment conditions include: a laser power density of 1000 W / cm 2 ~60000W / cm 2 , the laser wavelength is 600nm~1400nm.

[0023] The preparation method achieves efficient and stable electrode preparation through precise printing, drying, sintering and laser sintering processing steps. The close connection between the steps avoids unnecessary waste and repeated operations, and improves production efficiency. The laser sintering process promotes the further diffusion of silver silicon through laser-induced current, forming a good ohmic contact. This helps to reduce contact resistance and improve the current output and efficiency of solar cells. By optimizing the composition and ratio of the conductive paste and accurately controlling the conditions of sintering and laser sintering treatments, the preparation method can comprehensively achieve higher solar cell efficiency. Efficient electrode preparation helps to improve the photoelectric conversion efficiency of solar cells and reduce production costs. The stable compound layer and nano-scale tiny conductive channels formed during the sintering process enhance the wear resistance and weather resistance of solar cells. This helps to extend the service life of solar cells and improve their stability in harsh environments.

[0024] A fourth aspect of the present application provides a solar cell, comprising the front electrode described in the second aspect or the front electrode prepared by the preparation method described in the third aspect.

[0025] In some of the embodiments, the solar cell is referred to as a tunneling through oxide passivation solar cell.

[0026] Compared with the prior art, the present invention has the following advantages: Boron oxide in the conductive paste mainly forms a glass network structure with silicon dioxide to form a borosilicate glass system. At the same time, the viscosity of the high-temperature glass is adjusted to change its flow properties. Alkali metals such as lithium carbonate and sodium carbonate can easily disconnect the network structure of the glass, thereby reducing the viscosity of the glass and changing its high-temperature fluidity. At the same time, the addition of lithium and sodium alkali metals enhances the corrosiveness of the glass powder, which can effectively regulate the corrosion of the SiN film layer. By controlling the ratio of lithium and sodium, the thickness of the SiN film layer corroded by the glass powder can be precisely controlled. In particular, 1% to 5% gallium oxide materials have higher breakdown electric field strength and lower on-resistance, resulting in lower energy loss and higher conversion efficiency.

[0027] The above-mentioned conductive paste is a non-burn-through or semi-burn-through conductive paste that helps to corrode the SiN film layer to the thinnest layer at the nanoscale, or only partially corrodes the SiN film layer by reasonably matching the composition and proportion of the glass powder, thereby greatly protecting the SiN film layer and reducing the effect of carrier recombination, thereby increasing the opening voltage of the solar cell. After further laser-assisted sintering treatment, the interface diffusion between silver and silicon is enhanced, and a nanoscale tiny conductive channel can be formed between silver and silicon in a way of good ohmic contact points and reduced series resistance, thereby improving the efficiency of the solar cell. Combining the above-mentioned conductive paste, a higher opening voltage and higher solar cell efficiency can be achieved.

[0028] In addition, since the ohmic contact of the front electrode of the solar cell prepared with the above conductive paste can be formed by laser-excited silver-silicon diffusion, the effect of aluminum is greatly reduced. Therefore, the aluminum powder content in the conductive paste can be reduced, thereby reducing the chance of aluminum thorn formation and further improving the solar cell opening voltage. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 This is a SEM image of the silver-silicon interface that was mechanically broken apart in Example 11 of the present invention; Figure 2 is a SEM image of the silver-silicon interface milled by xenon plasma in Example 11 of the present invention; Figure 3 IV characteristic curve diagram for testing the battery cell of comparative example 2; Figure 4 The IV characteristic curve diagram for testing the battery cell of Example 11; Figure 5 Shown is a schematic diagram of the raw data of the electrical performance measurement of the battery cell of Example 11. DETAILED DESCRIPTION

[0030] The following is a further detailed description of the conductive paste, front electrode, solar cell and preparation method of the present application in combination with specific embodiments. The present application can be implemented in a variety of different forms and is not limited to the implementation methods described in this article. On the contrary, these implementation methods are provided to provide a more thorough and comprehensive understanding of the disclosure of this application.

[0031] All technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art, unless otherwise defined. The terms used in the description of the present invention are only for illustrating specific embodiments and are not intended to limit the present invention.

[0032] As used herein, "one or more" refers to any one, any two, or any two or more of the listed items.

[0033] In the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as an indication or suggestion of relative importance or quantity, nor can they be understood as an indication or implicit indication of the importance or quantity of technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. are only non-exhaustive descriptions for the purpose of enumeration and explanation, and the quantity should be understood as not constituting a closed limitation.

[0034] This application includes a closed technical solution consisting of the listed features, and also includes an open technical solution consisting of the publicly described technical features.

[0035] The present application relates to a numerical range, and unless otherwise specified, it is deemed to be continuous within the above numerical range, and includes the minimum and maximum values ​​within the range, as well as each value between the minimum and maximum values. The present application relates to a numerical range, and unless otherwise specified, it is deemed to be continuous. Further, each integer is included between the minimum and maximum values ​​in the interval, when the interval refers to an integer. In addition, this range can also be used in combination when multiple ranges are provided to describe features or characteristics. That is, unless otherwise specified, all ranges disclosed herein should be understood to include any class and all subclasses therein.

[0036] For solid-liquid mixing and solid-solid mixing, both refer to weight percentage, and for liquid-liquid mixing involved in this application, it refers to the percentage content by volume percentage. Unless otherwise specified, no special explanation is required.

[0037] The percentage concentrations involved in this application are based on the percentage concentrations unless otherwise specified. The final concentration refers to the ratio of the added component in the system after the component is added.

[0038] The temperature parameters in the present invention, in addition to the constant temperature treatment, can be treated with a certain temperature within a certain temperature range without special restrictions. The constant temperature treatment described below can make the temperature fluctuate within the accuracy range that the instrument can control.

[0039] The normal temperature in the present invention generally refers to 4°C to 30°C, preferably 20±5°C.

[0040] Terminology explanation: PV silver paste, that is, photovoltaic silver paste.

[0041] Non-burn-through solar cell materials: Silver powder has a smaller particle size, generally between 0.3 and 0.8 microns in non-burn-through photovoltaic silver paste. This smaller particle size means that the silver powder does not need to undergo high-temperature sintering during the preparation process. Preparation process: Unlike burn-through photovoltaic silver paste, non-burn-through photovoltaic silver paste does not require high-temperature sintering (generally between 500 and 800°C). It usually improves conductivity by adding materials such as flux. Since it does not undergo high-temperature sintering, non-burn-through photovoltaic silver paste usually does not burn through the thin film of the solar cell, so its solar cell stability is better.

[0042] LECO, Laser-enhanced contact optimization, is a laser-assisted sintering technology that separates the two key steps of passivation layer erosion and contact formation during high-temperature sintering through the highly concentrated energy and controllable characteristics of the laser, thereby achieving precise control of the sintering process.

[0043] FIB-SEM, or Focused Ion Beam Scanning Electron Microscope, is a high-resolution three-dimensional imaging and sample processing technology. It combines the Focused Ion Beam (FIB) and Scanning Electron Microscope (SEM) technologies to achieve precise processing, imaging and analysis of samples.

[0044] Some examples of the present invention provide a conductive paste for non-burn-through solar cells, including glass powder, silver powder, organic carrier, etc.

[0045] Specifically, by weight percentage, it includes the following components: Glass powder 0.5%~5%, Silver powder 80%~90% and Organic carrier 5%~15%.

[0046] The sum of the weight percentages of the above components is 100%.

[0047] The glass powder comprises the following components in terms of weight percentage: Lead oxide 40%~70%, Zinc oxide 5% to 20%, Silicon dioxide 1% to 15%, Bismuth oxide 1%~15%, Alumina 5% to 20%, Tungsten oxide 0%~5%, Gallium oxide 1% to 5%, Lithium carbonate 0%~5%, Sodium carbonate 0%~5%, Magnesium oxide 0%~5%.

[0048] The sum of the weight percentages of the above components is 100%.

[0049] The above conductive paste is a non-burn-through conductive paste, which can control the corrosion of the SiN film layer to be extremely thin to the nanometer level, or only partially corrode the SiN film layer, so that the effect of the SiN film layer in reducing carrier recombination is greatly protected. By reasonably matching the composition and ratio of the glass powder, the opening voltage of the solar cell is improved, and it is further protected after laser treatment, so that the wear resistance and wear resistance of the solar cell are enhanced. The interface diffusion between silver and silicon forms a nanometer-level tiny conductive channel between silver and silicon, the ohmic contact is good, and the series resistance is reduced, thereby improving the efficiency of the solar cell. In this way, the above conductive paste can comprehensively achieve a higher opening voltage and a higher efficiency of the solar cell.

[0050] In addition, since the ohmic contact of the front electrode prepared by the above conductive paste can be formed by laser-excited silver silicon diffusion, the effect of aluminum is greatly reduced, so the aluminum powder content in the paste can be reduced, thereby reducing the chance of aluminum thorn formation and further improving the opening voltage.

[0051] The principle of the present invention is as follows: glass powder is a key component of the conductive paste. During the sintering process, the glass powder reacts with the silicon wafer to form a stable compound layer, which helps to protect the SiN film from excessive corrosion. At the same time, the composition design of the glass powder can optimize the electrical properties of the solar cell, such as increasing the opening voltage. Silver powder is the main conductive component in the conductive paste and provides good conductive properties. During the laser processing process, the silver powder and the silicon wafer diffuse with each other to form a nanoscale tiny conductive channel, which enhances the ohmic contact and reduces the contact resistance, thereby improving the efficiency of the solar cell. The organic carrier is used to disperse the silver powder and the glass powder to ensure that the paste has good printing and sintering properties.

[0052] Crucially, the present invention uses LECO technology for non-destructive carrier injection, promoting the mutual diffusion of silver and silicon through induced current. The current formed by the laser is transmitted along a path with lower contact resistance, which reduces the contact resistance and optimizes the ohmic contact between silver and silicon. LECO technology can reduce the contact resistance between metal and semiconductor, improve the fill factor, and thus improve the efficiency of solar cells.

[0053] In the LECO process, lasers are used for non-destructive carrier injection, and the driving force of the process is the current induced by the LECO process. The current formed by the laser is transmitted along a path with lower contact resistance, causing the contact resistance to drop, thereby causing the interdiffusion of silver and silicon. The LECO technology can reduce the contact resistance between metal and semiconductor, improve the fill factor, and increase the efficiency of solar cells.

[0054] Specifically, the weight percentage of the glass powder includes, but is not limited to, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any range therebetween.

[0055] Specifically, the weight percentage of the silver powder includes, but is not limited to, 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90% or any range therebetween.

[0056] Specifically, the weight percentage of the organic carrier includes but is not limited to: 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any range therebetween.

[0057] Specifically, in the aforementioned glass powder, the weight percentage of lead oxide includes but is not limited to: 40%, 42%, 45%, 48%, 50%, 51%, 55%, 57%, 60%, 62%, 65%, 67%, 70% or a range therebetween.

[0058] Specifically, in the aforementioned glass powder, the weight percentage of zinc oxide includes but is not limited to: 5%, 7%, 10%, 11%, 12%, 13%, 15%, 16%, 18%, 19%, 20% or any range therebetween.

[0059] Specifically, the weight percentage of silicon dioxide in the glass powder includes, but is not limited to, 1%, 2%, 3%, 4.5%, 5%, 7%, 8%, 10%, 12%, 15% or any range therebetween.

[0060] Specifically, in the glass powder, the weight percentage of bismuth oxide includes, but is not limited to, 1%, 2.5%, 3%, 4%, 4.5%, 5%, 5.5%, 7%, 8%, 10%, 12%, 15% or any range therebetween.

[0061] Specifically, in the aforementioned glass powder, the weight percentage of aluminum oxide includes but is not limited to: 5%, 6%, 9%, 10%, 12%, 14%, 16%, 18%, 20% or any range therebetween.

[0062] Specifically, in the aforementioned glass powder, the weight percentage of tungsten oxide includes but is not limited to: 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8% or any range therebetween.

[0063] Specifically, in the glass powder, the weight percentage of gallium oxide includes, but is not limited to, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 6%, 7%, 8%, or any range therebetween.

[0064] Specifically, in the aforementioned glass powder, the weight percentage of lithium carbonate includes but is not limited to: 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or a range therebetween.

[0065] Specifically, in the aforementioned glass powder, the weight percentage of sodium carbonate includes but is not limited to: 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or a range therebetween.

[0066] Specifically, in the aforementioned glass powder, the weight percentage of magnesium oxide includes but is not limited to: 0%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or a range therebetween.

[0067] Some examples of glass powders calculated as weight percent include: Lead oxide 40%~65%, Zinc oxide 10%~20%, Silicon dioxide 3% to 8%, Bismuth oxide 3% to 8%, Alumina 8% to 15%, Tungsten oxide 0%~4%, Gallium oxide 1% to 4%, Lithium carbonate 0%~4%, Sodium carbonate 0% to 3% and Magnesium oxide 0%~3%.

[0068] The sum of the weight percentages of the above components is 100%.

[0069] Some of the examples where glass powder is measured in weight percent include: Lead oxide 51%~60%, Zinc oxide 10%~15%, Silicon dioxide 5% to 8%, Bismuth oxide 5% to 8%, Alumina 12% to 15% and Gallium oxide 1%~3%.

[0070] The sum of the weight percentages of the above components is 100%.

[0071] In some of the examples, the average particle size of the silver powder is 1 μm to 5 μm. Furthermore, the average particle size of the silver powder is 1 μm to 3 μm, and the specific surface area is 0.25 to 0.5 m2 / g. Without limitation, the silver powder mentioned above has a purity of 99.9% to 99.999%. In addition, there is no specific requirement for the shape of the silver powder, which can be spherical or scaly. The better shape should be spherical or nearly spherical.

[0072] In some examples, the glass powder has an average particle size of 0.5 μm to 3 μm and a softening point of 300 to 450° C.

[0073] Additionally, organic carriers are mentioned in some examples, including resins, solvents, and surfactants.

[0074] The resins described below are not limited and include one or more forms of resins such as polyvinyl alcohol type butyral resin, cellulose acetate butyrate resin, rosin type resin, propionate resin, etc. Further, the resin is a combination of polyvinyl alcohol type butyral resin, cellulose acetate butyrate resin, rosin type resin, and acrylic resin.

[0075] In some of the examples, the organic carrier may include the following component values ​​calculated by weight percentage.

[0076] Polyvinyl butyral resin 5% to 10%, Cellulose acetate butyrate resin 1% to 5%, Rosin resin 2% to 10%, Acrylic resin 2% to 15%, Solvent 60%~89.5%, Surfactant 0.5%~3%.

[0077] The sum of the weight percentages of the above components is 100%.

[0078] Specifically, the weight percentage of the polyvinyl butyral resin includes, but is not limited to, 5%, 6%, 7%, 8%, 9%, 10% or a range therebetween.

[0079] Specifically, the weight percentage of the cellulose acetate butyrate resin includes, but is not limited to, 1%, 2%, 3%, 4%, 5%, or any range therebetween.

[0080] Specifically, the weight percentage of rosin resin includes, but is not limited to, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10% or any range therebetween.

[0081] Specifically, the weight percentage of acrylic resin includes but is not limited to: 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15% or any range therebetween.

[0082] Specifically, the weight percentage of the solvent includes, but is not limited to, 60%, 65%, 70%, 72%, 74%, 75%, 76%, 80%, 85%, 89.5% or any range therebetween.

[0083] Specifically, the weight percentage of the surfactant includes, but is not limited to, 0.5%, 1%, 1.5%, 2%, 3% or any range.

[0084] Without limitation, the solvent is one or more, and the solvent is one or more of propylene glycol methyl ether acetate, propylene glycol butyl ether acetate, butyl carbitol, ethylene glycol monobutyl ether acetate, petroleum ether and dimethyl adipate.

[0085] The surfactant may be one or more of polydimethylsilicone oil, silicone surfactant, polyoxyethylene surfactant, oleamide, erucamide, dimethyl sulfoxide and polyether modified silicone oil.

[0086] Without limitation, the conductive paste can be prepared according to conventional methods in the art.

[0087] In some other examples of the present application, a front electrode is provided, comprising a solar cell silicon substrate and a conductive layer arranged on the solar cell silicon substrate, wherein the conductive layer is formed by printing and sintering the conductive paste as described above.

[0088] Furthermore, the conductive layer is prepared by sintering and laser processing the conductive paste as described above.

[0089] In another example of the present application, a method for preparing a front electrode of a solar cell is provided, comprising the following steps: Step 1, applying the conductive paste as described above to the surface of the silicon substrate of the solar cell, drying, sintering, and preparing an intermediate film; Step 2: performing laser sintering on the intermediate film to prepare a conductive layer.

[0090] In some of the examples, the sintering conditions include setting the temperature to 800° C. to 830° C.

[0091] In some of the examples, the laser sintering process conditions include: a laser power density of 1000 W / cm 2 ~60000W / cm 2 , the laser wavelength is 600nm~1400nm.

[0092] In the above scheme, the conductive paste (including glass powder, silver powder, organic carrier, etc.) described in the first aspect is printed onto the surface of the silicon substrate of the solar cell. This step ensures that the conductive paste can be evenly and accurately covered on the silicon substrate of the solar cell, laying the foundation for the subsequent drying and sintering steps.

[0093] Furthermore, the printed conductive paste is dried to remove the organic solvent and water therein. The drying step helps to solidify and stabilize the conductive paste and prevent deformation or shedding during the subsequent sintering process.

[0094] The sintering process is carried out at a temperature of 800℃ to 830℃. The sintering step allows the glass powder and silver powder in the conductive paste to react with the silicon wafer to form a stable compound layer, and promotes the mutual diffusion between silver and silicon to form nano-scale tiny conductive channels. The selection of the sintering temperature needs to ensure that the glass powder can fully melt and react with the silicon wafer, while avoiding excessively high temperatures that may damage the silicon wafer.

[0095] The sintered intermediate film is laser sintered to prepare a conductive layer. Laser sintering promotes further diffusion of silver silicon through laser-induced current, optimizes ohmic contact, and reduces contact resistance. The selection of laser power density and wavelength needs to ensure that the energy distribution and action depth of the laser can be accurately controlled to avoid excessive damage to the silicon wafer.

[0096] Specifically, the laser power density includes but is not limited to: 1000W / cm 2 , 1500W / cm 2 , 2000W / cm 2 、3000W / cm 2 , 5000W / cm 2 , 7000W / cm 2 , 9000W / cm 2 、10000W / cm 2 , 15000W / cm 2 、18000W / cm 2 , 20000W / cm 2 , 25000W / cm 2 、30000W / cm 2 、35000W / cm 2 , 40000W / cm 2 , 45000W / cm 2 , 50000W / cm 2 、55000W / cm 2 、60000W / cm 2 Or any range.

[0097] Specifically, the laser wavelength includes, but is not limited to, 600 nm, 650 nm, 700 nm, 750 nm, 800 nm, 850 nm, 900 nm, 950 nm, 1000 nm, 1100 nm, 1200 nm, 1300 nm, 1400 nm, or any wavelength range therebetween.

[0098] This method for preparing the front electrode of solar cells combines the advantages of traditional sintering and laser sintering. Traditional sintering: After applying a conductive paste (such as silver paste) to the surface of the silicon substrate of the solar cell, the intermediate film is prepared through drying and sintering steps. During this process, most of the organic solvent in the paste will evaporate, and the silver particles will form a preliminary contact with the surface of the silicon wafer. The sintering temperature is usually set at 800℃~830℃, and this temperature range helps to form good physical and electrical contact between silver and silicon wafers. Laser sintering: The intermediate film is laser sintered to further improve and optimize the performance of the conductive layer. Laser sintering uses the highly concentrated and controllable characteristics of the laser to accurately control the heat-affected zone and reduce thermal stress and potential damage to the silicon wafer. Laser power density and wavelength are key parameters. Laser power density is usually between 1000W / cm² and 60000W / cm², and laser wavelength is between 600nm and 1400nm.

[0099] Laser sintering can optimize metal contacts and reduce contact resistance, thereby obtaining higher current at the same line width or thinner lines at the same current. This helps to improve the conversion efficiency of solar cells. Laser sintering technology can control the heat-affected zone very accurately, making it possible to destroy the passivation layer and form metal contacts without damaging the active area of ​​the cell. This helps to maintain the stability and long-term performance of the cell. Due to the precision of laser sintering, thermal stress and potential damage to the silicon wafer can be reduced, thereby reducing the loss of the cell during the production process. The laser sintering process has a high degree of automation and can be integrated into high-speed production lines, which helps to improve the consistency and reliability of cell production. This method for preparing the front electrode of a solar cell combines the advantages of traditional sintering and laser sintering processing, and has significant advantages in improving cell efficiency, precise control, reducing cell loss, increasing production capacity and reliability, and reducing manufacturing costs.

[0100] In some other examples of the present application, a solar cell is provided, comprising the front electrode as described above or the front electrode prepared by the preparation method as described above.

[0101] In some examples, the solar cell is referred to as a tunnel oxide passivated solar cell.

[0102] The content of the present invention is described in detail below in conjunction with specific embodiments: The following are specific examples. Unless otherwise specified, the raw materials used in the examples are all commercially available products.

[0103] The silver powder used in the embodiment of the present invention has an average particle size of 1 μm to 2 μm, a purity of 99.99%, and is spherical.

[0104] The embodiment of the present invention adopts B30HHH type polyvinyl butyral resin purchased from Kuraray.

[0105] The cellulose acetate butyrate resin used in the examples of the present invention was purchased from ISMAN, model number CAB-551-0.01.

[0106] The rosin resin used in the embodiments of the present invention is SBR140 model purchased from Guangzhou Songbao Chemical Co., Ltd.

[0107] The acrylic resin used in the examples of the present invention is a BR-116 type product purchased from Mitsubishi Chemical Corporation.

[0108] The components and preparation method of the conductive paste are described in detail below in conjunction with specific embodiments: Example 1 This embodiment provides a conductive paste, the composition unit is weight percentage, specifically as follows: Glass powder 2.5%, Silver powder 89.3% and Organic carrier 8.2%.

[0109] Glass powder calculated as a percentage by weight, as contained in the next set of fractions.

[0110] Lead oxide 58%, Zinc oxide 13%, Silicon dioxide 6.5%, Bismuth oxide 6.5%, Alumina 13.5% and Gallium oxide 2.5%.

[0111] The preparation method of the conductive paste comprises the following steps: S1. Preparation of organic carrier: 10% by mass of polyvinyl butyral resin, 3% by mass of cellulose acetate butyrate resin, 5% by mass of rosin resin, and 10% by mass of acrylic resin are mixed, and 72% by mass of solvent propylene glycol methyl ether acetate is added, and the materials are stirred to dissolve at a temperature of 80°C. It takes about 1 hour to make the organic carrier uniform and transparent.

[0112] S2. Prepare glass powder: Put the weighed glass powder raw materials into a high-temperature muffle furnace controlled at 1200 degrees Celsius, stir them evenly with a mixer, and keep them warm for 1 hour to melt the materials. Pour deionized water into the molten glass slurry for quenching, grind the glass spheres into a particle size of about 0.5 microns to 3 microns, and then use a 400-mesh screen to sieve out impurities, dry them, and make glass powder for standby use.

[0113] S3. Prepare silver paste: The weight percentage of silver powder is 89.3%, and the weight percentage of organic carrier in the first step is 2.5%, and the weight percentage of glass powder in the second step is 8.2%, and the mixture is stirred evenly.

[0114] S4. Silver paste dispersion: put the raw materials after stirring evenly in step 3 into a three-roll grinder, grind them fully with different gaps and pressures for 5 times, and measure the fineness with a scraper fineness meter to be less than 8μm, so that the appearance is fine, uniform, and without obvious particles.

[0115] The preparation methods of the conductive pastes of Examples 2-7 and Comparative Examples 1-2 are the same as those of Example 1, the main difference being the different compositions, as shown in Table 1. The preparation methods of Examples 8-11 are the same as those of Example 1, the main difference being the different compositions, as shown in Table 1.

[0116] Table 1

[0117] Application Example 1 The present invention provides a TOPcon solar cell having the following preparation method.

[0118] An N-type silicon wafer that has completed the front-end process of TOPcon solar cells was selected, and the back main grid, back sub-grid, and front main grid of the TOPcon solar cell were printed on the silicon wafer in succession by screen printing. After drying, the conductive paste prepared in Example 1 was printed on the surface of the silicon wafer as the front sub-grid (i.e., the front electrode), and sintered in a chain high-temperature fast-firing furnace, with the high-temperature zone set at 830°C. After sintering, the solar cell was then laser treated.

[0119] The solar cell is loaded into the laser micro-guide processing equipment through a conveyor device and passed through the laser equipment with a laser power density of 50000W / cm 2 After being processed with a laser wavelength of 800nm, the solar cells flow out from the back of the device, are collected, and packaged to be tested for performance.

[0120] According to the above preparation method, TOPcon solar cells were prepared using the conductive pastes of Examples 2 to 7 and Comparative Examples 1 to 2, respectively.

[0121] Test Case Test method: The TOPcon solar cells were tested under standard test conditions using a German HALM-IV tester to obtain their open circuit voltage, short circuit current, series resistance, parallel resistance, fill factor and solar cell efficiency. The standard test conditions are: average ground illumination AM1.5; solar radiation power 1000W / ㎡; solar cell operating temperature 25℃.

[0122] The test results are shown in Table 2 below: Table 2

[0123] It can be concluded from Table 2 that, as a material for preparing TOPcon solar cells, the conductive paste material provided by the present invention meets the requirements in various performance tests (open circuit voltage, short circuit current, series resistance, parallel resistance, fill factor and solar cell efficiency).

[0124] Take the cell of the preferred embodiment 11 and observe the silver-silicon interface through FIB-SEM of TESCAN (a scientific instrument company). Figure 1 , it can be seen that silver and silicon have good contact; the picture is a scanning electron microscope image. The test parameters are: Speed: 2 (scanning speed), Mag: 7.00 kx (magnification, 7000 times), FoV: 39.8 μm (field of view width, 39.8 microns), WD: 10.47 mm (working distance, 10.47 mm), Scan Mode: ANALYSIS (scanning mode: analysis mode), Energy: 5 keV (acceleration voltage, 5 kiloelectron volts), Det: SE (detector type: secondary electron detector).

[0125] After TESCAN xenon plasma milling, the silver-silicon interface was observed using FIB-SEM. Figure 2 , it can be seen that there is a shallow transition layer at the silver-silicon interface, which can achieve good ohmic contact, reduce ohmic resistance, and achieve high photoelectric conversion efficiency. The picture is a scanning electron microscope image. The parameters are Speed: 3 (scanning speed), Mag: 29.9 kx (magnification, 29900 times), FoV: 9.32 μm (field of view width, 9.32 microns), WD: 4.96 mm (working distance, 4.96 mm), Scan Mode: UH-RESOLUTION (scanning mode: ultra-high resolution), Energy: 5 keV (acceleration voltage, 5 kiloelectron volts), Det: Mid-Angle BSE (detector type: mid-angle backscattered electron detector).

[0126] The IV characteristic curve of the battery cell of comparative example 2 is shown in FIG. Figure 3 It can be seen that the open circuit voltage Uoc of the battery cell is 0.732V, the short circuit current Isc is 13.463A, the fill factor FF is 85.134%, and the efficiency Eta [%]: is 25.424%.

[0127] The IV characteristic curve of the battery cell of Example 11 is shown in FIG. Figure 4 It can be seen that the open circuit voltage Uoc of the cell is 0.741V, the short circuit current Isc is 13.576A, the fill factor FF is 88.710%, and the efficiency Eta [%] is 27.029%. It can be seen that its electrical performance indicators are significantly better than those of comparative example 2, and the photoelectric conversion efficiency is increased by 1.6%.

[0128] Figure 3 and Figure 4 It is through measuring the current-voltage (IV) characteristic curve of solar cells under different light and temperature conditions. The current-voltage (IV) characteristic curve can obtain key parameters such as the open circuit voltage (Voc), short circuit current (Isc), maximum power point (MPP) and fill factor (FF) of the battery. Among them, Q1 hy1 is the forward scan curve, Q1 hy2 is the reverse scan curve, and Q1 mc is the fitted curve; the oblique line is the power and voltage curve that can be generated from the measured voltage and current data. The power and voltage curve shows the point of maximum power (Pmax).

[0129] Figures 3 to 5 In the diagram, Current refers to current, and Voltage refers to voltage.

[0130] Figure 5 The figure shows the schematic diagram of the raw data of the battery cell electrical performance measurement of Example 11. The computer software characterizes the battery performance by calculating the series resistance and parallel resistance of the battery through linear regression analysis, among which Q1 is a bright field forward measurement, Q2 is a dark field reverse measurement, Q3H is a high current dark field forward measurement, and Q3L is a low current dark field forward measurement. From the comparison of the four raw data, it can be seen that the open circuit voltage of the prepared TOPcon solar cell has been improved, thereby improving the efficiency of the solar cell.

[0131] The present invention also provides the following application examples: Application Example 2 The present invention provides a TOPcon solar cell having the following preparation method.

[0132] Select N-type silicon wafers that have completed the front-end process of TOPcon solar cells, and use screen printing to print the back main grid, back sub-grid and front main grid of TOPcon solar cells on the silicon wafers in turn. After drying, the conductive paste prepared in Example 2 is printed on the surface of the silicon wafer as the front sub-grid (i.e., the front electrode), which is sintered in a chain high-temperature fast-firing furnace. A high-temperature area of ​​820 degrees Celsius is set. After sintering, the solar cell is processed by laser equipment.

[0133] The solar cell is loaded into the laser micro-guide processing equipment through a conveyor device and passed through the laser equipment with a laser power density of 5000W / cm 2 After the laser treatment with a wavelength of 1300nm, the solar cells flow out from the back of the device, are collected, and packaged to be tested for performance. TOPcon solar cells are obtained.

[0134] Application Example 3 The present invention provides a TOPcon solar cell having the following preparation method.

[0135] An N-type silicon wafer that has completed the front-end process of TOPcon solar cells was selected, and the back main grid, back sub-grid, and front main grid of the TOPcon solar cell were printed on the silicon wafer in succession by screen printing. After drying, the conductive paste prepared in Example 4 was printed on the surface of the silicon wafer as the front sub-grid (i.e., the front electrode), and sintered in a chain high-temperature fast-firing furnace, with the high-temperature zone set at 805°C. After sintering, the solar cell was then laser treated.

[0136] The solar cell is loaded into the laser micro-guide processing equipment through a conveyor device and passed through the laser equipment with a laser power density of 20000W / cm 2 After the laser treatment with a wavelength of 1100nm, the solar cells flow out from the back of the device, are collected, and packaged to be tested for performance. TOPcon solar cells are obtained.

[0137] The various technical features in the above embodiments can be combined arbitrarily. In order to make the description concise, the various technical features in the above embodiments do not describe all possible combinations. However, as long as there is no contradiction in the combination of these technical features, they should be considered as the scope recorded in this description.

[0138] The above implementation examples only describe several implementation methods of the application, so as to facilitate a specific and detailed understanding of the technical solution of the application, but it cannot be understood as limiting the scope of protection of the patent application. It should be noted that for ordinary technicians who belong to the scope of protection in this aspect and do not deviate from the application concept in this aspect, some deformation and improvement can also be made. It should be understood that on the basis of the technical solution provided in this application, those skilled in the art can obtain limited experimental technical solutions within the scope of protection of the claims attached to this application according to logical analysis, reasoning or technical solutions.

Claims

1. A non-burn-through solar cell conductive paste, characterized in that: include: Glass powder, silver powder and an organic carrier; the glass powder comprises the following components by weight percentage: Lead oxide 40%~70%, Zinc oxide 5% to 20%, Silicon dioxide 1% to 15%, Bismuth oxide 1%~15%, Alumina 5% to 20%, Tungsten oxide 0%~5%, Gallium oxide 1% to 5%, Lithium carbonate 0%~5%, Sodium carbonate 0%~5%, Magnesium oxide 0%~5%.

2. The non-burn-through solar cell conductive paste according to claim 1, characterized in that: The glass powder comprises the following components by weight percentage: Lead oxide 40%~65%, Zinc oxide 10%~20%, Silicon dioxide 3% to 8%, Bismuth oxide 3% to 8%, Alumina 8% to 15%, Tungsten oxide 0%~4%, Gallium oxide 1% to 4%, Lithium carbonate 0%~4%, Sodium carbonate 0%~3%, Magnesium oxide 0%~3%.

3. The non-burn-through solar cell conductive paste according to claim 1, characterized in that: The glass powder comprises the following components by weight percentage: Lead oxide 51%~60%, Zinc oxide 10%~15%, Silicon dioxide 5% to 8%, Bismuth oxide 5% to 8%, Alumina 12%~15%, Gallium oxide 1%~3%.

4. The non-burn-through solar cell conductive paste according to claim 1, characterized in that: Calculated by weight percentage: Glass powder 0.5%~5%; Silver powder 80%~90%; Organic carrier 5%~15%.

5. The non-burn-through solar cell conductive paste according to claim 4, characterized in that: The average particle size of the silver powder is 1 μm to 5 μm, and the specific surface area is 0.25 to 0.5 m 2 / g; The average particle size of the glass powder is 0.5 μm to 3 μm, and the softening point is 300 to 450°C.

6. The non-burn-through solar cell conductive paste according to claim 4, characterized in that: Organic carriers include resins, solvents and surfactants; The resin is one or more of polyvinyl alcohol type butyral resin, acetate type cellulose butyrate resin, rosin type resin and acrylic resin.

7. The non-burn-through solar cell conductive paste according to claim 6, characterized in that: The organic carrier comprises, by weight percentage: Polyvinyl butyral resin 5% to 10%, Cellulose acetate butyrate resin 1% to 5%, Rosin resin 2% to 10%, Acrylic resin 2% to 15%, Solvent 60%~89.5%, Surfactant 0.5%~3%.

8. A solar cell front electrode, characterized in that: The solar cell comprises a silicon substrate and a conductive layer arranged on the silicon substrate, wherein the conductive layer is formed by printing and sintering the non-fire-through solar cell conductive paste according to any one of claims 1 to 7.

9. A method for preparing a front electrode of a solar cell, characterized in that: The following steps are involved: Printing the non-burn-through solar cell conductive paste according to any one of claims 1 to 7 on the surface of a solar cell silicon substrate, drying, sintering, and manufacturing an intermediate film; Performing laser sintering on the intermediate film to prepare a conductive layer; The sintering conditions include: setting the temperature to 800°C to 830°C; The conditions for laser sintering treatment include: laser power density of 1000W / cm 2 ~60000W / cm 2 , the laser wavelength is 600nm~1400nm.

10. A solar cell, characterized in that: The solar cell front electrode comprises the solar cell front electrode as claimed in claim 8.

Citation Information

Patent Citations

  • Electric conduction slurry and application of electric conduction slurry in N type silicon wafer solar cells

    CN104795127A

  • Solar cell front surface electrode paste

    CN108428492A

  • Crystalline silicon solar cell front silver paste and preparation method thereof

    CN108766618A

  • Ceramic glass powder and solar cell metallization slurry containing glass powder

    CN114213018A

  • Glass powder for front silver paste of solar cell

    CN115611519A